Tomato (Lycopersicum commune) Juice and Physical Exercise Increase Number of Neurons and ER? expression in Post-Ovariectomy Rats Brain - Laswati, Hening; Subadi, Imam; Andriana, Meisy; Kurniawati, Patricia Maria; Pangkahila, Jahya Alex (BALI MEDICAL JOURNAL, 2016)
Background: Estrogen deficiency condition can degrade the quality of life, decline in cognitive function will be more severe trough age. Phytoestrogen compounds can be found in pegaga leaf extract, tomatoes, and papaya is an easy and inexpensive way to increase estrogen levels in post menopause women through extra gonadal estrogen induction. Therefore, the aims of this study were to examine the effect of tomato juice, physical exercise, and combination of these treatments on promoting neurons and ER? expression in somatosensory cortex that contribute to cognitive function of post-ovariectomy rats. Method: Twenty-eight female healthy Wistar rats (Rattus novergicus), 8-10 weeks old, from Laboratory of Biochemistry, Faculty of Medicine Airlangga University include in this experiment. The animals were housed in the animal-care facility with ad libitum food and water. The temperatur was maintained at 18°C-24°C. The treatments were done 2 weeks after ovariectomy. Tomato were made in Laboratory of Pharmacognocy and Phytochemistry, Faculty of Pharmacy, Airlangga University, from inner part of the tomato fruits (mucous like substance) with freeze dry method (-40°C). Results: The weight of white rat Rattus norvegicus post ovariectomy in this study was between 133-170 gram with a mean weight 154.32 ± 9.72 gram. Hematoxylin/eosin staining showed neuronal deficit in the control rats brain. In figure 1, the tomato group showed the largest of neurons number (145.43 ± 17.728), followed the combination group (140.57 ± 22.449), the exercise group (136.86 ± 23.104) and the smallest number in the control group (96.43± 28.965). Four weeks after treatments the number of neurons increased significant in the tomato group (p=0.001), exercise group (p=0.004) and combination group (p=0.002) from the control group. This study showed no significant different between tomato and exercise group (p=0.500), tomato and combination group (p=0.701) and between exercise and combination group (p=0.769). Conclusions: In conclusion, our data demonstrated that post ovariectomy rats showed deficit numbers of neurons and decreased ER? in the somatosensory cortex. Treatment with physical exercise, tomato juice, and combination of these treatments increased the number of neurons and ER? expression in the somatosensory cortex.